TGFβ Regulation of Perilacunar/Canalicular Remodeling Is Sexually Dimorphic. (13th May 2020) - Dole, Neha S; Yee, Cristal S; Mazur, Courtney M; Acevedo, Claire; Alliston, Tamara
ABSTRACT: Bone fragility is the product of defects in bone mass and bone quality, both of which show sex‐specific differences. Despite this, the cellular and molecular mechanisms underpinning the sexually dimorphic control of bone quality remain unclear, limiting our ability to effectively prevent fractures, especially in postmenopausal osteoporosis. Recently, using male mice, we found that systemic or osteocyte‐intrinsic inhibition of TGFβ signaling, achieved using the 9.6‐kb DMP1 promoter‐driven Cre recombinase (TβRII ocy−/− mice), suppresses osteocyte perilacunar/canalicular remodeling (PLR) and compromises bone quality. Because systemic TGFβ inhibition more robustly increases bone mass in female than male mice, we postulated that sex‐specific differences in bone quality could likewise result, in part, from dimorphic regulation of PLR by TGFβ. Moreover, because lactation induces PLR, we examined the effect of TGFβ inhibition on the female skeleton during lactation. In contrast to males, female mice that possess an osteocyte‐intrinsic defect in TGFβ signaling were protected from TGFβ‐dependent defects in PLR and bone quality. The expression of requisite PLR enzymes, the lacunocanalicular network (LCN), and the flexural strength of female TβRII ocy−/− bone was intact. With lactation, however, bone loss and induction in PLR and osteocytic parathyroid hormone type I receptor (PTHR1) expression, were suppressed in TβRII ocy−/− bone, relative to the control littermates. Indeed, differential control of PTHR1 expression, by TGFβ and other factors, may contribute to dimorphism in PLR regulation in male and female TβRII ocy−/− mice. These findings provide key insights into the sex‐based differences in osteocyte PLR that underlie bone quality and highlight TGFβ signaling as a crucial regulator of lactation‐induced PLR. © 2020 American Society for Bone and Mineral Research.